Determining the characteristics of diffracted waves of small amplitude around a vessel in shallow water - Efremova, Nina; Nilva, Alexander; Kotovskaya, Nataliya; Dryha, Marina (Eastern-European Journal of Enterprise Technologies, 2017)
The vessels at outer anchorage are exposed to the influence of a complex system of waves. This system is formed by the incident and diffracted waves. In order to examine characteristics of a wave field around the vessel, which floats idling at outer anchorage, we solved two problems. The first problem is determining the velocity potential of diffracted wave motion, caused by the incidence at arbitrary angle of regular waves with small amplitude to a stationary vessel under conditions of shallow water. The solution is executed by the matched asymptotic expansion method (MAEM). The region filled with fluid is conditionally divided into the internal and external zones. In both zones, separate boundary problems are stated, and they are considerably simpler than the initial boundary problem for the entire region. The solutions of the problems are asymptotically merged at the border of zones. The second problem is defining the characteristics of waves near a vessel. From the expression for a speed potential we derived the equation of perturbed free surface. The calculations are conducted of the waves’ amplitudes in the assigned points around the vessel. The variable parameters are the depth of water area, wavelength and a course angle of waves. The examples of wave fields are given. Determining the characteristics of a wave field transformed by the vessel is important for planning the operation of auxiliary ships (tugboats, bunkering vessels, pilot and port roads boats, as well as oil/garbage collector boats and boom crafts). This work is connected with the safety of traffic in the open sea (transfer of people and loads from one vessel to another) and with ecological safety (elimination of oil and petroleum spills). Wave height is the limiting factor for operating the auxiliary vessels, which is why determining it properly is a necessary task.